Novel zinc(II) phthalocyanine conjugates bearing different numbers of BODIPY and iodine groups as substituents on the periphery - Gol, Cem; Malkoc, Mustafa; Yeşilot, Serkan; Durmuş, Mahmut (Elsevier Sci Ltd, 2014)
The novel zinc (II) phthalocyanine (Pc)-boron dipyrromethene (BODIPY) conjugates bearing one, two, three or four BODIPY units on the phthalocyanine framework were synthesized by the reaction of 4,4'-difluoro-8-(4-ethynyl)-phenyl-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene (Ethynyl-BODIPY) with 2(3),9(10),16(17),23(24)-tetrakis(iodo) zinc(II) phthalocyanine (Iodo-Pc) using the Pd catalyzed Sonogashira-coupling reaction. The newly synthesized Pc-BODIPY conjugates were fully characterized by elemental analysis, H-1 and C-13 NMR, MALDI-TOF mass, FT-IR, UV-Vis and fluorescence spectroscopic techniques. The photophysical and photochemical properties of these conjugates were investigated by means of absorption and fluorescence spectroscopies in DMSO solutions for the determination of their photodynamic therapy (PDT) efficiency. The photoinduced energy transfer process of these novel conjugates was also explored in tetrahydrofuran solution. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Asymmetric phthalocyanine; BODIPY; Panchromatic; Fluorescence; Energy transfer; Singlet oxygen